Pup and bear - Banks, Kate, 1960- (Schwartz & Wade Books, 2017)
A stranded wolf cub is rescued and raised by a loving polar bear, and years later when he is grown into a wolf and on his own, he comes upon a lost polar bear cub, and the cycle begins again.